A = 1 - 2 - 3 + 4 + 5 - 6 - 7 + ... + 2008 + 2009 - 2010 - 2011
A = ( 1 - 2 - 3 + 4 ) + ( 5 - 6 - 7 + 8 ) + ... + ( 2005 - 2006 - 2007 + 2008 ) + ( 2009 - 2010 - 2011 )
A = 0 + 0 + ... + 0 + ( -2012 )
A = -2012
\(A=1-2-3+4+5-6-7+8-...+2005-2006-2007-2008+2009-1010-2011\)
\(< =>A=\left(1-2-3+4\right)+\left(5-6-7+8\right)+...+\left(2009-2010-2011\right)\)
\(< =>A=0+0+...+2009-2010-2011\)
\(< =>A=2009-4021=-2012\)
A = (1 - 2 - 3 + 4) + (5 - 6 - 7 + 8) + ... + (2005 - 2006 - 2007 + 2008) + (2009 - 2010 - 2011)
A = 0 + 0 + ... + 0 + (-2012)
A = -2012
Vậy A = -2012